Capacity improvements for rural single wire earth return systems - Wolfs, Peter (IEEE, 2005)
The single wire earth return, (SWER), system is a low cost power distribution method that finds international use in rural areas. It is a key technology for the extension of grid systems. In Australia, SWER systems can cover vast areas. A single SWER system may typically supply 100kW to several dozen customers and may extend more than 300km. Recent changes in the Australian retail energy market structure and significant load growth are driving a requirement for new low cost methods of capacity improvement. Shunt reactors are often used in SWER systems to compensate for line charging current effects. As voltage regulation is the determining capacity factor, the replacement of fixed shunt reactors with controllable reactors provides an opportunity to significantly increase the system capacity. A case study of the North Jericho SWER system is presented which shows a capacity increase of approximately 85%can be achieved.